A 100 MHz 6th Order Continuous Time Band-Pass Sigma Delta Modulator with Active Inductor based Resonators - Dobson, Kevin; Ahmadi, Shahrokh; Zaghloul, Mona (European Journal of Applied Sciences, 2015)
This paper presents a 6th order, continuous time band-pass Sigma Delta modulator in IBM 0.18 um CMOS technology. We replace traditional RLC circuits, containing low quality factor spiral inductors with high quality factor, active inductor based resonators utilizing negative impedance circuits. Pad to pad simulation of the extracted layout in Cadence yields an enhanced SNDR of 78 dB with a noise bandwidth of 18 kHz and a power consumption of 12 mW. Our modulator occupies 7.5 mm2 of chip area with pads.